Effect of Oil Circulation Rate on the Performance of Compressor in Electric Vehicle Air-conditioning - Tao Hong; Zhang Ting; Wu Shengli; Cheng Yingnan; Miao Jian; Shao Xinhong (Zhileng xuebao)
To investigate the effect of the oil circulation rate (OCR) on the performance of a variable-speed scroll compressor (R134a) for electric vehicle air-conditioning, elaborate experiments were conducted to obtain the performance and OCR in a test bench using a secondary fluid calorimeter and OCR measurement by a separator. The results show that the OCR significantly influences the scroll compressor performance when speeds of 3 000 r/min, 4 500 r/min, and 6 000 r/min are compared under two heavy-load conditions. More specifically, when the OCR is between 1% and 10% under the same condition, the volume efficiency and electrical efficiency decline by 0.02–0.05, whereas both the discharge temperature and shell temperature rise by 5–15 K as the OCR decreases from 10% to 1%. This occurs at every speed, and it is especially evident at low speed. Generally, a moderate OCR should be near 5% because an OCR that is less than 5% has a higher impact than that greater than 5%.